Outcomes of Acute Respiratory Distress Syndrome in Mechanically Ventilated Patients With Cirrhosis. (September 2019) - Boente, Ryan D.; Sheikh, Adil; Bosslet, Gabriel T.; Ghabril, Marwan S.
Abstract : Objective: To better describe the outcomes of acute respiratory distress syndrome in mechanically ventilated patients with cirrhosis. Design: Single-center, retrospective study of mechanically ventilated patients with cirrhosis between 2008 and 2015. Setting: ICU at a large academic medical and transplant center. Patients: One hundred eighty-one mechanically ventilated patients with cirrhosis. Interventions: Demographic and clinical data were reviewed, and acute respiratory distress syndrome was identified per Berlin criteria. We compared demographic and clinical characteristics on ICU admission in patients with and without acute respiratory distress syndrome. The primary endpoint was hospital mortality (including discharge to hospice). Mortality risk was stratified by Chronic Liver Failure-Sequential Organ Failure Assessment and Model for End-Stage Liver Disease. Measurements and Main Results: The mean age in 181 eligible patients was 53 ± 11 years; 67% were male; and 91% were Caucasian. In all, n = 35 (19%) of mechanically ventilated patients had acute respiratory distress syndrome. They were more frequently female (46% vs 30%; p = 0.08), with suspected infection (86% vs 53%; p < 0.001), and had higher mean Model for End-Stage Liver Disease (32 vs 24; p < 0.001) and Chronic Liver Failure-Sequential Organ Failure Assessment (15 vs 11; p < 0.001) than patients without acute respiratory distress syndrome. Hospital mortality was higher in patients with (40%) versus without (22%) acute respiratory distress syndrome ( p = 0.03). In the risk-adjusted analysis (for Model for End-Stage Liver Disease, Chronic Liver Failure-Sequential Organ Failure Assessment and age), acute respiratory distress syndrome was not independently associated with hospital mortality (odds ratio, 0.80; CI, 0.3–2.5; p = 0.7). Conclusions: Acute respiratory distress syndrome is common in mechanically ventilated patients with cirrhosis but is not independently associated with increased mortality. Abstract : Supplemental Digital Content is available in the text.